2018
DOI: 10.1007/s00442-018-4242-z
|View full text |Cite
|
Sign up to set email alerts
|

Rodents, not birds, dominate predation-related ecosystem services and disservices in vertebrate communities of agricultural landscapes

Abstract: To understand the relationship between conservation measures and agricultural yields, we need to know the contributions of organisms to both ecosystem services and disservices. We studied the activity and contribution of birds and mammals to intermediate ecosystem services (predation of weed seeds or invertebrate pests) and disservices (predation of crop seeds or beneficial invertebrates) in southern Sweden between June and November 2016. We measured seed and invertebrate predation rates using trays placed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 57 publications
2
26
0
Order By: Relevance
“…Land cover near to the feeders did not appear to have a direct effect on estimated rat populations. This accords with a study in Southern Sweden where activity of rodents was also not affected by surrounding habitat or landscapes (Tschumi et al 2018). Nevertheless, brown rats were more abundant in cultivated land and grass and less abundant in forested areas in Hunan Province, China (Xiao et al 2018).…”
Section: Understanding the Primary Drivers Of Brown Rats Associated Wsupporting
confidence: 90%
“…Land cover near to the feeders did not appear to have a direct effect on estimated rat populations. This accords with a study in Southern Sweden where activity of rodents was also not affected by surrounding habitat or landscapes (Tschumi et al 2018). Nevertheless, brown rats were more abundant in cultivated land and grass and less abundant in forested areas in Hunan Province, China (Xiao et al 2018).…”
Section: Understanding the Primary Drivers Of Brown Rats Associated Wsupporting
confidence: 90%
“…However, birds may contribute less to predation than other vertebrates in the study system and the observed patterns for vertebrate predation may primarily stem from predation by small mammals (Tschumi et al. , and see, e.g., Holmes and Froud‐Williams , Fischer et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…The most common predatory vertebrates in the study system are small mammals followed by some species of birds (Tschumi et al. ). Eighty small holes (diameter 1 mm) were drilled into each tray to allow rainwater to runoff.…”
Section: Methodsmentioning
confidence: 99%
“…However, trees and shrubs might greatly enhance natural enemy communities by providing additional trophic resources and sites for reproduction, overwintering and estivation (Stamps and Linit, 1998), especially in older systems (> 15-20 years). Higher trophic taxa such as birds and small mammals have also been shown to benefit from the presence of tree rows and UVS in alley cropping systems (Klaa et al, 2005;Gibbs et al, 2016), and their effects on weed and invertebrate pest suppression are mixed (Tschumi et al, 2018). Besides, agroforestry farmers are currently using contrasting strategies for UVS management (e.g.…”
Section: Future Research On Biological Control In Alley Cropping Agromentioning
confidence: 99%